2016
DOI: 10.1021/acsami.6b05099
|View full text |Cite
|
Sign up to set email alerts
|

Bypassing Protein Corona Issue on Active Targeting: Zwitterionic Coatings Dictate Specific Interactions of Targeting Moieties and Cell Receptors

Abstract: Surface functionalization strategies for targeting nanoparticles (NP) to specific organs, cells, or organelles, is the foundation for new applications of nanomedicine to drug delivery and biomedical imaging. Interaction of NPs with biological media leads to the formation of a biomolecular layer at the surface of NPs so-called as "protein corona". This corona layer can shield active molecules at the surface of NPs and cause mistargeting or unintended scavenging by the liver, kidney, or spleen. To overcome this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 35 publications
0
86
0
Order By: Relevance
“…Recent studies have revealed that the formation of a protein corona on the surface of liposomes can lead to an inhibition of targeting efficacy, as the targeting-peptides can be hidden from their receptors [40], [41], [42], [43]. We have therefore conducted a study to see if incubation of t-L-ALD with mouse serum will compromise the targeting efficiency, in an attempt to correlate the in vitro targeting efficiency with in vivo active targeting in a living mouse.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that the formation of a protein corona on the surface of liposomes can lead to an inhibition of targeting efficacy, as the targeting-peptides can be hidden from their receptors [40], [41], [42], [43]. We have therefore conducted a study to see if incubation of t-L-ALD with mouse serum will compromise the targeting efficiency, in an attempt to correlate the in vitro targeting efficiency with in vivo active targeting in a living mouse.…”
Section: Discussionmentioning
confidence: 99%
“…For example, corona-free nanoparticles were developed with tunable hydrophobicity that serve as platforms to enhance desirable nanobiological behaviour, such as cellular uptake and haemolysis 137 . In addition, silica nanoparticles conjugated with biotin and cysteine were introduced to suppress corona-associated mistargeting, wherein cysteine was used as a zwitterionic ligand 138 . In this study, it was reported that a zwitterionic surface aids targeting.…”
Section: Using Nanomaterials In Living Subjectsmentioning
confidence: 99%
“…[109] www.advancedsciencenews.com www.advhealthmat.de particles. [118,122] Particles functionalized with zwitterionic cysteine and biotin showed reduced protein adsorption, and biotin-mediated cell uptake after incubation with HP was higher than for targeted particles without the zwitterionic coating. [118] Strategies and opportunities for tuning the protein corona on the carrier surface with regard to the performance of an active-targeting drug carrier will be discussed in detail in the next section.…”
Section: Wwwadvancedsciencenewscom Wwwadvhealthmatdementioning
confidence: 97%